Experimental Development To Determine Time Constant For Polymer Collector - Mohd Rosli, Mohd Afzanizam; Mat, Sohif; Sopian, Kamauzzaman; Salleh, Elias; Sharif, Mohd Khairul Anuar (Asian Research Publishing Network (ARPN), 2018)
The presents study presents an experimental development to determine the time constant for the polymer collector under hot and humid climate in Malaysia.The experimental setup has been conducted at the Taman Inovasi Teknologi Hijau,Universiti Kebangsaan Malaysia (UKM).It used water as a working fluid and conducted according the ASHRAE Standard 93-2010 (Methods of testing to determine the thermal performance of solar collectors).The closed system of experiment rig was equipped with heat exchanger and auxiliary heater to control the water inlet temperature from the polymer collector to ensure it close with the ambient temperature (Ti ≈ Ta) during an experiment.The available polymer collector in the market was used with minor modification was developed by inserting an insulator underneath the collector.This able to reduce the heat losses on the bottom part of collector to the environment.It shows the time constant of modified polymer collector was 90 seconds during the test day.The information of the time constant of polymer collector is vital to conduct an experiment of quasi steady state thermal performance of the polymer collector.It also provides the information of the collector behavior under transient condition during outdoor experiment.For example,the effect of the water and surface temperature once the irradiance change abruptly.